"Neural efficiency" of experts` brain during judgment of actions: A high-resolution EEG study in elite and amateur karate athletes - Babiloni, C.; Marzano, N.; Infarinato, F.; Iacoboni, M.; Rizza, G.; Aschieri, P.; Cibelli, G.; Soricell, A.; Euseb, F.; Del Percio, C. (Behavioural Brain Research, 2020)
Here we tested two working hypotheses on spatially selective cortical activation ("neural efficiency") in experts: (i) compared to non-athletes, elite karate athletes are characterized by a reduced cortical activation during the judgment of karate actions; (ii) compared to non-athletes and elite karate athletes, amateur karate athletes are characterized by an intermediate cortical activation during the judgment of karate actions. Electroencephalographic (EEG) data were recorded in 16 elite karate athletes, 15 amateur athletes and 17 non-athletes. They observed a series of 120 karate videos. At the end of each video, the subjects had to judge the technical/athletic level of the exercise by a scale from 0 to 10. The mismatch between their judgment and that of the coach indexed the degree of action judgment. The EEG cortical sources were estimated by sLORETA. With reference to a pre-stimulus period, the power decrease of alpha (8-12 Hz) rhythms during the video indexed the cortical activation (event-related desynchronization, ERD). Regarding the hypothesis of reduced activity in elite karate athletes, low- and high-frequency alpha ERD was less pronounced in dorsal and "mirror" pathways in the elite karate athletes than in the non-athletes. Regarding the hypothesis of intermediate cortical activity in amateur karate athletes, low- and high-frequency alpha ERD was less pronounced in dorsal pathways across the non-athletes, the amateur karate athletes, and the elite karate athletes. In conclusion, athletes` judgment of observed sporting actions is related to less pronounced alpha ERD, as a possible index of "neural efficiency" in experts engaged in social cognition.